(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Cholera is an acute infectious intestinal disease caused by Vibrio cholerae. The main clinical manifestations of the disease are severe watery diarrhea and vomiting, which within a short period lead to severe dehydration and electrolyte imbalance in the body. This article scientifically analyzes the etiology, pathogenesis, epidemiological characteristics, clinical course, diagnosis, treatment, and prevention of cholera.